Description of an independently developed quality assessment tool to meet emergency department credentialing and Emergency Ultrasound Fellowship Accreditation Council guidelines - Vu, Michael; Gordon, Richard; Miller, Sara; Larimore, Katheryn; Bakunas, Carrie; Morris, Victoria; Walsh, Ryan; Karfunkle, Benjamin (The Ultrasound Journal, 2026)
Background: Quality assurance (QA) review is essential to any point-of-care ultrasound (POCUS) program that credentials emergency clinicians or hosts an Emergency Ultrasound Fellowship Accreditation Council (EUFAC) accredited fellowship. Commercially designed QA solutions exist but may not be accessible to all programs due to budgetary or institution-specific administration constraints.Objectives: The authors aimed to develop a robust, standalone, HIPAA-compliant POCUS QA database which satisfies both credentialing requirements and EUFAC review goals.Methods: An indexed, searchable electronic QA database was developed using Google workspace. The database was inspected reviewer disagreement trends that led to feedback at the individual and departmental level and was used to satisfy QA review requirements for ultrasound fellows.Results: Since deployment of the database in July 2021, 2742 studies have undergone QA review out of approximately 15,000 studies performed (18.3%). Reviewers disagreed with some portion of the interpretation in 848 (24.8%) exams, most commonly abdominal aortic aneurysm evaluation (n = 45 exams, 31.1%) and basic echocardiography (n = 1203 exams, 27.9%). Disagreement was least common for male genitourinary exams (n = 19 exams, 0%) and advanced echocardiograms (n=57, 15.8%), likely reflecting operator experience. For 209 (7.6%) studies, feedback to the clinicians was warranted and delivered via direct communication. This process has resulted in department-level education in consistently deficient areas.Conclusion: We present our lightweight, easily reproducible alternative to commercial POCUS QA solutions that has led to targeted feedback and department-level education while also satisfying accreditation requirements.